2008
DOI: 10.1152/ajpheart.01355.2007
|View full text |Cite
|
Sign up to set email alerts
|

A novel signaling pathway of ADP-ribosyl cyclase activation by angiotensin II in adult rat cardiomyocytes

Abstract: ADP-ribosyl cyclase (ADPR-cyclase) produces a Ca(2+)-mobilizing second messenger, cADP-ribose (cADPR), from NAD(+). In this study, we investigated the molecular basis of ADPR-cyclase activation in the ANG II signaling pathway and cellular responses in adult rat cardiomyocytes. The results showed that ANG II generated biphasic intracellular Ca(2+) concentration increases that include a rapid transient Ca(2+) elevation via inositol trisphosphate (IP(3)) receptor and sustained Ca(2+) rise via the activation of L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…Knockout of PI3K-␥ in mice, or transfection of small interfering RNA against PI3K-␥ in ␤-cells, significantly inhibits glucose-stimulated insulin secretion (37). The partial inhibition in the [Ca 2ϩ ] i response and complete inhibition in BLX-1002-induced insulin secretion by the specific PI3K inhibitor suggest that this kinase may be involved both in the regulation of [Ca 2ϩ ] i (19,40) and insulin exocytosis (16). Considering that the PI3K inhibitors wortmannin and LY-294002 have no selectivity for individual PI3K isoforms (28) and that different isoforms of PI3K may play different roles in insulin secretion (16,37), the PI3K isoform involved in BLX-1002-induced insulin secretion requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of PI3K-␥ in mice, or transfection of small interfering RNA against PI3K-␥ in ␤-cells, significantly inhibits glucose-stimulated insulin secretion (37). The partial inhibition in the [Ca 2ϩ ] i response and complete inhibition in BLX-1002-induced insulin secretion by the specific PI3K inhibitor suggest that this kinase may be involved both in the regulation of [Ca 2ϩ ] i (19,40) and insulin exocytosis (16). Considering that the PI3K inhibitors wortmannin and LY-294002 have no selectivity for individual PI3K isoforms (28) and that different isoforms of PI3K may play different roles in insulin secretion (16,37), the PI3K isoform involved in BLX-1002-induced insulin secretion requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 expression has been reported in some systemic arteries, including aorta and the coronary and renal arteries (8)(9)(10). Endogenous vasoconstrictors, such as norepinephrine, endothelin-1 (ET-1), and angiotensin II (Ang II), have been shown to activate the cyclase and catalase activities of CD38, contributing to the elevation of [Ca 21 ] i and vasoconstriction (11)(12)(13)(14)(15)(16). In general, these vasoconstrictory agonists of G-protein-coupled receptors activate phospholipase C (PLC) to synthesize inositol trisphosphate (IP 3 ) and diacyglycerol from phosphatidylinositol bisphosphate.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Ϫ/Ϫ and CD38 ϩ/ϩ cardiomyocytes but that 8-Br-cADPR completely inhibited the ANG II-induced sustained Ca 2ϩ increase, indicating that cADPR is generated by a novel ADPR-cyclase (8). We also demonstrated that the kidney ADPR-cyclase-selective blocking compound 4,4Ј-dihydroxyazobenzene (DHAB) protects ANG II-mediated mesangial cell growth (16).…”
mentioning
confidence: 79%